Coinfection with Bartonella clarridgeiae and Bartonella henselae and with different Bartonella henselae strains in domestic cats. - Gurfield, A N (1997)
Bartonella clarridgeiae and several strains of Bartonella henselae, the agent of cat scratch disease, with variations in the 16S rRNA gene have been found to infect the blood of cats. An epidemiologic study of Bartonella infection in domestic French cats revealed that of 436 cats sampled, 5 cats (1.1%) were coinfected with B. henselae and B. clarridgeiae and 2 cats (0.5%) were coinfected with two strains of B. henselae with variations in the 16S rRNA gene, B. henselae type I and type II. In an indirect immunofluorescence assay, coinfected cats tested positive for both Bartonella species at titers of > or = 128. Identification of the colonies was achieved by preformed enzyme analysis, PCR-restriction fragment length polymorphism analysis of the citrate synthase gene, and 16S rRNA gene sequencing. Colony size differences in mixed culture allowed differentiation of the Bartonella species. The coinfection of cats with two Bartonella species or variants of the same species raises concern about the possibility of dual infection in humans. The development of a polyvalent vaccine targeted against the most pathogenic or invasive strains may be a means of protecting cats and man from infection.